HUBUNGAN STRATEGI DIGITAL STORYTELLING DENGAN MINAT BACA DAN KEMAMPUAN MENULIS KREATIF SISWA KELAS V - Rakha Athaya, Muhammad; Mumpuni, Atikah; Saefudin Wahid, Farhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the digital storytelling strategy and students’ reading interest as well as creative writing skills among fifth-grade students at SD Negeri Slatri 01. This research is motivated by the relatively low level of students’ reading interest and the suboptimal development of creative writing skills, such as difficulties in expressing ideas, developing story plots, and limited vocabulary mastery, alongside the underutilization of digital technology in learning. This study employed a quantitative method with a correlational design. The population consisted of 37 students, all of whom were selected as the sample using a saturated sampling technique. Data were collected through questionnaires and tests, while data analysis included descriptive statistics, prerequisite tests (normality and linearity), and Pearson Product Moment correlation analysis using SPSS software. The results showed that descriptively, the implementation of the digital storytelling strategy was in the fairly good category, students’ reading interest was relatively high, and creative writing skills were in the good category. The prerequisite test results indicated that the data were normally distributed and had a linear relationship. The correlation test revealed a positive, strong, and highly significant relationship between the digital storytelling strategy and reading interest (r = 0.652; sig = 0.000 < 0.01). Meanwhile, the relationship with creative writing skills was positive, weak to moderate, but significant (r = 0.337; sig = 0.041 < 0.05). Based on these findings, it can be concluded that the digital storytelling strategy is related to both variables, although other contributing factors still influence the outcomes, particularly in creative writing skills.